TI_GERICHTE 52.2006.259 vom 5. Oktober 2006 , Licenza edilzia per sopraelevare uno stabile nel nucleo (concessione di una deroga) - TI Tribunale d'appello (2006)
Licenza edilzia per sopraelevare uno stabile nel nucleo (concessione di una deroga)